2020
DOI: 10.1002/pbc.28345
|View full text |Cite
|
Sign up to set email alerts
|

Financial toxicity of childhood cancer and changes to parents’ employment after treatment completion

Abstract: Objective: Childhood cancer can have short-and long-term impacts on parents' finances and employment. It is important to understand how families adjust to the financial and employment changes caused by childhood cancer, the ongoing impacts after treatment completion, and which families need more targeted support. Qualitative research is necessary to facilitate an in-depth understanding of the employment and financial impacts on families and to capture parents' complex and nuanced experiences and perspectives. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
53
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 43 publications
3
53
0
1
Order By: Relevance
“…For example, parents expressed a will to work 'where it mattered', for example within childcare and healthcare. Similar findings of wanting to make a difference in their work life have also been found among mothers and fathers of children with cancer in Australia (Kelada et al, 2020). In the Australian study, this was reported among parents with the highest socioeconomic status (Kelada et al, 2020), a pattern that was not evident in this study.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…For example, parents expressed a will to work 'where it mattered', for example within childcare and healthcare. Similar findings of wanting to make a difference in their work life have also been found among mothers and fathers of children with cancer in Australia (Kelada et al, 2020). In the Australian study, this was reported among parents with the highest socioeconomic status (Kelada et al, 2020), a pattern that was not evident in this study.…”
Section: Discussionsupporting
confidence: 84%
“…In addition to struggling to find a sustainable balance between different roles, the parents in this study also expressed that the child's illness had changed their view of the importance of their life roles, with the parent role making up for a larger proportion of what they perceived to be important in how they spent their time. They described how the experience of having a seriously ill child has made them better parents, and emphasized a will to be present with their children to a larger extent than before, which mirrors previous research (Kelada et al, 2020;Lindahl Norberg & Steneby, 2009;Long & Marsland, 2011;Peikert et al, 2020;Tan et al, 2020). A rather unexpected finding was that parents reported not only having changed their priorities in relation to the balance between the parent role and the work role, but also that the experience of caring for a seriously ill child had led some parents to re-evaluate what their work life should consist of.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Employer behavior and workplace characteristics affected parents’ ability to return to work, and could serve as either facilitators or barriers. As previously shown, 20,21 flexibility of the workplace was a key factor for work participation. This suggests that employers could preferably allow as much flexibility as possible, something that the distance work imposed at most Swedish workplaces during the coronavirus pandemic has shown to be possible in more workplaces than what has previously been considered.…”
Section: Discussionmentioning
confidence: 61%
“…Parents' experiences of cancerrelated financial toxicity should also be discussed as part of standard care, and referral made to professional services and community organisations that are able to provide assistance. 10…”
Section: Implications For General Practitionersmentioning
confidence: 99%